2018
DOI: 10.1002/jbmr.3642
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Homeostasis in Murine Fetuses Is Sensitive to Maternal Calcitriol but Not to Absence of Fetal Calcitriol

Abstract: Vitamin D receptor (VDR) null fetuses have normal serum minerals, parathyroid hormone (PTH), skeletal morphology, and mineralization but increased serum calcitriol, placental calcium transport, and placental expression of Pthrp, Trpv6, and (as reported in this study) Pdia3. We examined Cyp27b1 null fetal mice, which do not make calcitriol, to determine if loss of calcitriol has the same consequences as loss of VDR. Cyp27b1 null and wild‐type (WT) females were mated to Cyp27b1+/‐ males, which generated Cyp27b1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“… 6–9 Studies of Vdr null and Cyp27b1 null fetal mice, 10–12 and Cyp27b1 null Hannover pigs, 13 have shown that the absence of either VDR or calcitriol does not affect fetal serum calcium, phosphorus, magnesium, and parathyroid hormone (PTH); amniotic fluid mineral content (a surrogate of renal mineral excretion); and skeletal morphology, mineral content, and gene expression. Placental calcium transfer was normal in vitamin D-deficient rat fetuses, 9 Cyp27b1 null fetal mice, 12 and Cyp27b1 null fetal Hannover pigs. 13 Conversely, placental calcium transport was increased in Vdr null mice, which had high serum calcitriol concentrations that presumably acted on an alternate receptor to stimulate transport.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“… 6–9 Studies of Vdr null and Cyp27b1 null fetal mice, 10–12 and Cyp27b1 null Hannover pigs, 13 have shown that the absence of either VDR or calcitriol does not affect fetal serum calcium, phosphorus, magnesium, and parathyroid hormone (PTH); amniotic fluid mineral content (a surrogate of renal mineral excretion); and skeletal morphology, mineral content, and gene expression. Placental calcium transfer was normal in vitamin D-deficient rat fetuses, 9 Cyp27b1 null fetal mice, 12 and Cyp27b1 null fetal Hannover pigs. 13 Conversely, placental calcium transport was increased in Vdr null mice, which had high serum calcitriol concentrations that presumably acted on an alternate receptor to stimulate transport.…”
Section: Introductionmentioning
confidence: 91%
“… 2 , 14 Catabolism by CYP24A1 results in 40-fold higher concentrations of 24,25(OH) 2 D as compared to calcitriol in human cord blood 19–21 and in fetal rodents and lambs. 22–24 In our prior studies of fetal mice, 24,25(OH) 2 D was 54-fold higher than calcitriol and 3 times higher than maternal 24,25(OH) 2 D. 12 Postnatally, high CYP24A1 activity in neonatal rodents and lambs continues to catabolize 25OHD and contributes to low levels of calcitriol. 25 , 26 Collectively, these studies suggest that developmental programming maintains low serum calcitriol until the intestines are ready to respond to calcitriol after birth.…”
Section: Introductionmentioning
confidence: 95%
“…This procedure was developed to enable measurement of vitamin D metabolites in limited pediatric serum samples from idiopathic infantile hypercalcemia (IIH) patients and have even applied it to individual mice in animal studies, rather than having to pool serum from several animals. (24,25) Accurate assay still depends upon the availability of pure, deuterium-labeled internal standards, many of which can be purchased commercially, as well as calibration solutions for each analyte. In some cases (eg, 25-OH-D 3 -26,23-lactone), deuterium-labeled internal standards are not readily available and must be chemically synthesized by research-based collaborators, but a demand for these to be made commercially usually creates a market for some company to fill.…”
Section: Advent Of Lc-ms/ms To Revolutionize Vitamin D Assaymentioning
confidence: 99%
“… 4 , 7–18 Serum calcium, phosphorus, PTH, and the endochondral skeleton are also normal in severely vitamin D-deficient fetal rats, 19–21 Vdr null fetal mice, 22 , 23 and Cyp27b1 null fetal mice. 24 …”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that Cyp27b1 null fetal mice, which do not make calcitriol, had normal serum calcium and phosphate, PTH, FGF23, skeletal mineral content, tibial lengths and morphology, and placental calcium transport. 24 When we directly compared fetal littermates of Cyp27b1 null dams, they were biochemically and phenotypically indistinguishable from each other, despite their differing genotypes. This was also true for fetal littermates of related WT dams.…”
Section: Introductionmentioning
confidence: 99%